Taxonomic novelties in Gomidesia clade (Myrcia s.l., Myrtaceae) from the Atlantic Forest of Brazil - Amorim, Bruno S.; Alves, Marccus (Phytotaxa, 2016)
Two new species of Myrcia from the Atlantic Forest of southeastern Brazil are here described and illustrated. Morphological features set them in the Gomidesia clade. Myrcia espiritosantensis and M. ruschii are recorded from southeastern Brazil, which is considered the diversity center for the genus Myrcia, and the species have restricted distribution in submontane and montane forests. Conservation assessments based on IUCN criteria are also given.